Numerical and experimental investigations on sandwich panels made with eco-friendly components under low-velocity impact. (January 2022) - Oliveira, Pablo; Kilchert, Sebastian; May, Michael; Panzera, Tulio; Scarpa, Fabrizio; Hiermaier, Stefan
A low-velocity impact characterisation of a sustainable sandwich panel based on upcycled bottle caps as circular honeycomb is conducted. The recycled core aims to develop an alternative route of reusing waste bottle caps disposed in landfills. Ecological alternatives to skin (recycled PET foil) and adhesive (bio-polyurethane) are also compared with classic components (aluminium skin and epoxy polymer). A low-cost reinforcement (cement particles) is also proposed to enhance the mechanical strength of the panel. The samples are tested at several levels of impact energy, according to the type of skin, to observe their effect on mechanical behaviour. Metal skins achieve higher impact loads and energy absorption compared to PET foil. The bio-adhesive leads to a similar or enhanced maximum impact load and energy absorption compared to the epoxy adhesive. Specific properties highlight the promising performance of the bio-based adhesive with aluminium skins, reaching increments of up to 378%. The cement increases the maximum load and reduces the duration of the impact event, leading to lower energy absorption. The unreinforced epoxy polymer shows a visible adhesive peeling off from aluminium skin, while particle inclusions lead to reduced overall delamination. Biopolymer exhibits marginal adhesive debonding and stable deformation, revealing a progressive failure. In general, PET samples show core shear failure due to rupture of the skin. Crack propagation in PET samples made with biopolymer adhesive is reduced at lower energy levels. The results evidence the promising application of bottle caps in a more sustainable honeycomb core to build eco-friendly structures.